Inpatient Cognitive Behavior Therapy for Adolescents with Anorexia Nervosa: Immediate and Longer-Term Effects - Dalle Grave, Riccardo; Calugi, Simona; El Ghoch, Marwan; Conti, Maddalena; Fairburn, Christofer G. (Frontiers in Psychiatry, 2014)
Introduction: Inpatient treatment for anorexia nervosa is often successful in restoring body weight, but a high percentage of patients relapse following discharge. The aim of the present study was to establish the immediate and longer-term effects of a novel inpatient program for adolescents that was designed to produce enduring change. Method: Twenty-seven consecutive patients with severe anorexia nervosa were admitted to a 20-week inpatient treatment program based upon enhanced cognitive behaviour therapy (CBT-E). The patients were assessed before and after hospitalization, and six and 12 months later. Results: Twenty-six patients (96%) completed the program. In these patients there was a substantial improvement in weight, eating disorder features and general psychopathology that was well maintained at 12-month follow-up. Conclusions: These findings suggest that inpatient CBT-E is a promising approach to the treatment of adolescents with severe anorexia nervosa.